Coconut-derived D-xylose affects postprandial glucose and insulin responses in healthy individuals - Bae, Yun Jung (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2011)
Metabolic alterations including postprandial hyperglycemia have been implicated in the development of obesity-related diseases. Xylose is a sucrase inhibitor suggested to suppress the postprandial glucose surge. The objectives of this study were to assess the inhibitory effects of two different concentrations of xylose on postprandial glucose and insulin responses and to evaluate its efficacy in the presence of other macronutrients. Randomized double-blind cross-over studies were conducted to examine the effect of D-xylose on postprandial glucose and insulin response following the oral glucose tolerance test (OGTT). In study 1, the overnight-fasted study subjects (n = 49) consumed a test sucrose solution (50 g sucrose in 130 ml water) containing 0, 5, or 7.5 g D-xylose powder. In study 2, the overnight-fasted study subjects (n = 50) consumed a test meal (50 g sucrose in a 60 g muffin and 200 ml sucrose-containing solution). The control meal provided 64.5 g of carbohydrates, 4.5 g of fat, and 10 g of protein. The xylose meal was identical to the control meal except 5 g of xylose was added to the muffin mix. In study 1, the 5 g xylose-containing solutions exhibited significantly lower area under the glucose curve (AUCg) and area under the insulin curve (AUCi) values for 0-15 min (P < 0.0001, P < 0.0001), 0-30 min (P < 0.0001, P < 0.0001), 0-45 min (P < 0.0001, P < 0.0001), 0-60 min (P < 0.0001, P < 0.0001), 0-90 min (P < 0.0001, P < 0.0001) and 0-120 min (P = 0.0071, P = 0.0016). In study 2, the test meal exhibited significantly lower AUCg and AUCi values for 0-15 min (P < 0.0001, P < 0.0001), 0-30 min (P < 0.0001, P < 0.0001), 0-45 min (P < 0.0001, P = 0.0005), 0-60 min (P = 0.0002, P = 0.0025), and 0-90 min (P = 0.0396, P = 0.0246). In conclusion, xylose showed an acute suppressive effect on the postprandial glucose and insulin surges.